MENGURANGI KETIMPANGAN, MELURUSKAN ESENSI PEMBANGUNAN - Wijayanto Samirin (Universitas Paramadina, 2014)
Over the last one decade, Indonesian economy has becomeinteresting topic in the global economic arena, especially concerning itsability to perfome well despite the global economic turbulence. When othercountries experienced difficulty, Indonesian economy was able to maintaineconomic growth.Unfortunately, despite the above encouraging news, it is still unclearwhose actually enjoy the increase of the economic pie. In fact, incomeinequality grew fast and booked its highest record in 2012. The situationbecome more challenging since the above inequality is also accompanied bythe high wealth and land ownership inequality.There are few theories that could justify the incidence of the increasein inequality in Indonesia, in short the theories shows that inequality is aprocess toward prosperity. However, various studies also indicate that theabove logic are not applicable for Indonesia.Indonesia is entering a crucial time, to rethinking its economicdesign. Without accompanied by economic equality, high economic growthwill not able to improve life quality. In fact, this may reduce the socialcohesion among people, a serious situation for a pluralistic nation likeIndonesia. Inequality should be reduced, constitution and nationalphilosophy should be reflected in various Government policies.This paper describe and discuss economic inequality in Indonesia,several relevant theories concerning inequality, impact of inequality, lessonlearned fro other countries, as well as several recommendation to addressiunequality issue in Indonesia.